Two new nematode species of the genus Tobrilus Andrássy, 1959 (Nematoda, Triplonchida) from Lake Baikal, Russia - Naumova, Tatyana V.; Gagarin, Vladimir G. (European Journal of Taxonomy, 2019)
Two new nematode species of the genus Tobrilus Andrássy, 1959 from Lake Baikal are described and illustrated. The first species Tobrilus elginus sp. nov. was found in the littoral zone of Maloye More Bays. The second species Tobrilus juliae sp. nov. dwells on bodies of dead sponges Lubomirskia baicalensis (Pallas, 1776). Tobrilus elginus sp. nov. is most similar to T. amabilis Tsalolikhin, 1974 and T. bekmanae Tsalolikhin, 1975. In contrast to the first species it has a shorter body and spicules, longer gubernaculum and a shorter supplements row. Its body is shorter and thinner, tail and supplement row are shorter and the vulva is more posterior as compared to the second species. The body size of Tobrilus juliae sp. nov. is most similar to T. securus Gagarin & Naumova, 2011 and T. saprophagus Naumova & Gagarin, 2017. From the first of these species it differs by the thinner body, shorter tail, comparatively shorter outer labial setae and shorter spicules. It differs from the second species by a thinner body, shorter male tail and shorter labial setae.